Outcome differences of starting Paxlovid for COVID-19 within or after five days of symptoms onset in the elderly: a retrospective study - Chen, Junjun; Yang, Quanjun; Xu, Xiaohong; Wu, Xia; Han, Yonglong; Guo, Cheng; Yang, Jiao (The Journal of Infection in Developing Countries, 2024)
Introduction: The study aimed to compare the outcomes of nirmatrelvir and ritonavir drug combination (Paxlovid) therapy in patients who received treatment within or after five days of COVID-19 confirmed in the elderly. Methodology: This was a single-center, retrospective cohort study of older COVID-19 patients (≥ 60 years) admitted from April 7 to May 30, 2022. Patients were categorized into the EP group (starting Paxlovid within five days) and the LP group (starting Paxlovid after five days) following symptoms onset. Length of stay and positive SARS-CoV-2 duration were compared between the two groups. Severe case conversion from mild and moderate COVID-19 patients were also analyzed. Results: In total, 273 patients were included: 137 in the EP group and 136 in the LP group. Compared to the LP group, the EP group had a significantly shorter length of stay (12.4 vs. 14.7 days, p = 0.001) and positive SARS-CoV-2 duration (11.7 vs. 15.8 days, p < 0.001). The EP group had lower severe case conversion (4.4% vs. 15.4%, p = 0.002). Additionally, abnormal IL-6 and lower lymphocyte count indicated increased length of stay. Older age was associated with a decreased risk in SARS-CoV-2 negative test (HR = 0.98) and an increased risk in severe case conversion (OR = 1.11). Conclusions: Starting Paxlovid within five days of COVID-19 symptoms onset reduced the length of stay and SARS-CoV-2 duration compared to initiating treatment after five days. While severe case conversion among mild COVID-19 patients might be comparable whether starting Paxlovid within or after five days.